The Role of the Social Worker in Identifying the Problem of Visual Impairment and Its Impact on Academic Achievement Among Preparatory School Students - Nofle, Marwa Rhwma; Al Garbazi, Salah Belaid; Karim, Mona Mosbah; Eghfaier, Ambarkh Atiya; Thobot, Salma Atiya; Khaleefah, Sanaa Ali; Elghanemi, Fatima Saad (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The current research aims to know the role of the social worker in identifying the problem of the visually impaired and its impact on the academic achievement of middle school students in some educational institutions in the city of Zliten, as well as to identify the problems that hinder the work of the social worker in the educational institution for the problem of low vision and its impact on academic achievement, and to identify appropriate solutions for the social worker in dealing with the problem of the visually impaired for middle school students, and the researchers relied on the descriptive approach using the social survey, and it has been adopted On the questionnaire form as a performance for data collection, it was applied to social workers, where the total population swallowed (14) individuals and then distributed the questionnaire to (14) members of the sample. Perhaps the most important findings of this research are: The primary role is to inform teachers of the individual differences of visually impaired students. Relying on more than one technique while dealing with students who have low vision. Strengthening the bonds between parents and the educational institution during professional work and improving the relationship with teachers within the educational institution. The lack of a special office to study, diagnose and treat students who have problems, as well as the failure of the educational institution to organize training courses to raise the efficiency of the social worker. Failure to report by parents to students who have poor vision to the management of the institution. The guardian should give a note if the student has poor vision to the social worker’s office. Paying attention to early medical detection for all students and raising awareness of healthy lunch suitable for the visually impaired.